Gereja dan Kaum Bapak: Sebuah Tinjauan Metode Pendampingan Kognitif-Behavioral Bagi Kaum Bapak di HKBP Pearaja - Lumbantobing, Arthur (Sekolah Tinggi Diakones HKBP, 2021)
Mentoring is an essential method in Pastoral Care Service. Unfortunately, the mentoring method is often neglected by counselors in mentoring services. As a result, the meeting between counselors and counselee didn’t lead the counselee to the expected change. This Journal is a literature study and field research on cognitive-behavioral mentoring methods for fathers who rarely attend church on Sunday at HKBP Pearaja, Tarutung. In this journal, the author critics the importance of reviewing the mentoring method in providing assistance to fathers who attend church rarely. Furthermore, the author tried to show that the cognitive–behavioral mentoring method equip the fathers to be a priesthood, role model, and teacher in Christian families. In addition, through the cognitive-behavioral method, the church can equip the fathers to bring spiritual growth to a better way. With this paper, the author also offers a contextual approach to seek cognitive-behavioral mentoring methods for fathers